Current Advances and Therapeutic Potential of Agents Targeting Dipeptidyl Peptidases-IV, -II, 8/9 and Fibroblast Activation Protein - Chen, Shu-Jen; Jiaang, Weir-Torn (Current Topics in Medicinal Chemistry, 2011)
Dipeptidyl peptidase-IV (DPP-IV), a serine protease that specifically cleaves the N-terminal dipeptide with a preference for L-proline or L-alanine at the penultimate position, is involved in the degradation of incretin hormones, including glucagon-like peptide-1 (GLP-1) and glucose-dependent insulinotropic polypeptide (GIP). GLP-1 regulates glucose homeostasis by stimulating insulin secretion, inhibiting glucagon release, and delaying gastric emptying. Intravenous GLP-1 has been shown to increase insulin secretion in response to elevated glucose levels and offers therapeutic benefit for patients with type 2 diabetes. However, the therapeutic application of GLP-1 is severely compromised by its lack of oral activity and its rapid degradation by plasma DPP-IV. Consequently, small-molecule DPP-IV inhibitors that could extend the duration of action of GLP-1 and prolong its beneficial effects have been investigated as promising therapeutics for type 2 diabetes. This review summarizes important structural classes of DPP-IV inhibitors, focusing mainly on their inhibitory potency and selectivity for DPP-IV over other related peptidases such as DPP-II, DPP8, DPP9, and FAP. Because inhibition of DPP8 and/or DPP9 has been shown to cause severe toxicity in preclinical species, high selectivity is an important criterion in selecting DPP-IV inhibitors for clinical development. As of today, several DPP-IV inhibitors have completed phase III clinical studies for the treatment of type 2 diabetes. A brief overview of clinical efficacy data on these inhibitor drugs is provided here. In addition, biological activities of other related dipeptidyl peptidases (DPP-II, DPP8, DPP9, and FAP) will be summarized. Selective inhibitors for these peptidases and their therapeutic potential will be discussed.
Keywords: drug development